2016
DOI: 10.1111/jpi.12302
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: the dawning of a treatment for fibrosis?

Abstract: Fibrosis is a common occurrence following organ injury and failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 112 publications
(289 reference statements)
5
74
0
2
Order By: Relevance
“…However, these parameters were significantly reduced in CRS animals after receiving either melatonin or exendin‐4 treatment and further reversed by combined melatonin–exendin‐4 treatment. Intriguingly, a review article has recently emphasized that melatonin exhibits its antifibrotic effects in the heart, liver, lung, kidney, and other organs through multiple protective signaling pathways . In this way, our finding is consistent with this report, suggesting that melatonin may well have a future in the treatment of fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…However, these parameters were significantly reduced in CRS animals after receiving either melatonin or exendin‐4 treatment and further reversed by combined melatonin–exendin‐4 treatment. Intriguingly, a review article has recently emphasized that melatonin exhibits its antifibrotic effects in the heart, liver, lung, kidney, and other organs through multiple protective signaling pathways . In this way, our finding is consistent with this report, suggesting that melatonin may well have a future in the treatment of fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…The antifibrotic effect of melatonin has been confirmed in rats exposed to continuous light, isoproterenol treatment, myocardial infarction, doxorubicin, N‐nitro‐L‐arginine‐methyl ester (L‐NAME) treatment, and chronic intermittent hypoxia . Inhibition of fibrosis is a commonly observed action of melatonin . Our results, for the first time, confirmed that melatonin treatment remarkably reversed collagen deposition in the perivascular and interstitial areas of the left ventricle following TAC surgery.…”
Section: Discussionsupporting
confidence: 75%
“…Melatonin has been shown to influence various hepatic cell types, such as hepatocytes, hepatic stellate cells, and cholagiocytes, and the existence of melatonin receptors in the liver also emphasizes its importance in liver pathophysiology . Previously, melatonin was proven to counteract oxidative stress , inflammatory responses , and apoptosis in experimental liver fibrosis models . We have previously demonstrated that melatonin could suppress necroptotic cell death and autophagy during liver fibrosis and ischemia/reperfusion respectively.…”
Section: Introductionmentioning
confidence: 99%